PEMANFAATAN E-LEARNING BAGI PARA PENDIDIK DI ERA DIGITAL 4.0 UTILIZATION OF E-LEARNING FOR EDUCATORS IN DIGITAL ERA 4.0 - Ike Yustanti; Dian Novita (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
In this digital era or Industrial 4.0 revolution, technological advances become things that cannot be solved in human life. Teachers must learn better in learning, need to utilize optimal learning resources, this is important, because the effectiveness of learning is also included by the willingness and ability to utilize learning media, such as the web (google class). In this era students are required to have certain skills, besides those educators are also required to have several competencies that must be possessed so that the e-learning program that they run can run well. An educator or teacher must be able to learn to be there to learn, be creative and fun.